PENGATURAN PENGANGKATAN SEKRETARIS DAERAH UNTUK MEWUJUDKAN NETRALITAS PEGAWAI NEGERI SIPIL DAERAH - I Gede Pranajaya (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
Governance and development efforts to implement national and local levels can run smoothly largely depends on the perfection of the State apparatus, which in its function must be professional and neutral character of the influence of all groups and political parties, and does not discriminate in providing services to the community in order to realize the welfare of society. To realize the neutrality of the State Apparatus, the central government is trying to give a neutral space of the apparatus of government both at central and local levels, however, the reality is often found to realize it is not easy. Various allegations of lack of neutrality of State Apparatus including regional secretary still often expressed by the public, especially during the General Election of Regional Head and Deputy Head of the candidates came from previously elected regional head (incumbent). It is not separated from the vagueness of the norm (vogue norm), associated with the filling of the post of secretary of the province are included in the Position Leader High as stipulated in Article 19 paragraph (3) of Law No. 5 of 2014 on the Reform of Civil State, stating for High leadership positions defined competency requirements, qualifications, rank, education and training, track record position and integrity, as well as other necessary requirements. The above provisions are not clear in stating the requirements that must be met by candidates for secretary of the province to ensure neutrality. This study is a normative law research that examines the ingredients literature that primary legal materials and secondary law. This study uses the approach of legislation and approach the concept. In the data collection is done by steps searches theories, concepts, principles, and an inventory of rule of law relating to the research problem. The conclusion relating to the cases in this study, namely charging Position Leader Higher done in an open and competitive among Civil Servants by taking into account the requirements of competence, qualifications, rank, education and training, track record positions, and intergitas and other requirements needed in accordance with the legislation reflects to realize the secretaries of provincial officials were neutral.